Field notes contributed by Bery Engebretsen, summer 2004 - Engebretsen, Beryet al (2004)
List of birds and locations contributed by Berry Engebretsen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2004. Epson - sheet feed